The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1007/978-3-030-58858-8_22
|View full text |Cite
|
Sign up to set email alerts
|

Dependencies of Agile Teams – An Analysis of the Scaled Agile Framework

Abstract: Context: Agile teams are small teams with 3 to 9 members. In complex development endeavors such as systems engineering, an agile team has many dependencies, since it is not possible to incorporate all specialist skills into one team. Frameworks like the Scaled Agile Framework (SAFe) describe how agile teams operate in a larger setting. Objective: The aim of this study is to analyze how agile teams collaborate with their organizational environment. Method: We analyzed SAFe to investigate how much guidance it pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…That, in turn, might lead to overburdening business teams and service streams; particulars of collaboration between agile teams remain an issue as well. 28 Kasauli et al place communication-and knowledge management-related challenges in the very center of scaled agile approaches with respect to requirements engineering. 9 Their work also brings up the issues that companies have when meeting security-attributable and other nonfunctional requirements.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…That, in turn, might lead to overburdening business teams and service streams; particulars of collaboration between agile teams remain an issue as well. 28 Kasauli et al place communication-and knowledge management-related challenges in the very center of scaled agile approaches with respect to requirements engineering. 9 Their work also brings up the issues that companies have when meeting security-attributable and other nonfunctional requirements.…”
Section: Related Researchmentioning
confidence: 99%
“…Having extra stakeholders in place upon scaling the Scrum approach with SAFe potentially implies changing the focus, length, and scope of meetings. That, in turn, might lead to overburdening business teams and service streams; particulars of collaboration between agile teams remain an issue as well 28 . Kasauli et al place communication‐ and knowledge management‐related challenges in the very center of scaled agile approaches with respect to requirements engineering 9 .…”
Section: Related Researchmentioning
confidence: 99%
“…Nonetheless, as the vast majority of software development projects are unique, they cannot be properly supported by any off‐the‐shelf framework implemented in its original, textbook format 4–13 . Besides, not all organizations are ready to fully implement any framework in a one‐time shift regarding organizational, cultural, and technical aspects, 13,14 whereas there are no gradual approaches or guidelines for large‐scale agile transformation 15,16 . Indeed, previous studies have reported numerous challenges while adopting such frameworks, 4,6,17 including a mismatch between framework and organization, 6,7,13 controversies within the framework, 18–20 complex organization setup, 15,20 changes in management structure, 6,15,19,21,22 fluctuating company's policies, 15,19,21 and change resistance 15,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] Besides, not all organizations are ready to fully implement any framework in a one-time shift regarding organizational, cultural, and technical aspects, 13,14 whereas there are no gradual approaches or guidelines for large-scale agile transformation. 15,16 Indeed, previous studies have reported numerous challenges while adopting such frameworks, 4,6,17 including a mismatch between framework and organization, 6,7,13 controversies within the framework, [18][19][20] complex organization setup, 15,20 changes in management structure, 6,15,19,21,22 fluctuating company's policies, 15,19,21 and change resistance. 15,19,20 Not surprisingly, it has been acknowledged that agile methods often need to be tailored to accommodate specific situations [6][7][8]12,14,[23][24][25] or issues (e.g., risk management).…”
mentioning
confidence: 99%